Vestiges of an orb-weaving ancestor? The “biogenetic law” and ontogenetic changes in the webs and building behavior of the black widow spider Latrodectus geometricus (Araneae Theridiidae) - Eberhard Chabtree, William G. (2008)
Young juveniles of L. geometricus fit the strong trend for “ontogeny to repeat phylogeny” previously documented in other web-building spiders; younger spiders were less likely to build the derived silk retreats that occur at the edges of webs of adults. Younger individuals also consistently builtç more highly organized webs, with radial lines that converge on a central, horizontal disc and that support regularly spaced, sticky “gumfoot” lines. Some details of how radial and gumfoot lines were built suggest that the radial and gumfoot lines and the behavior involved in their construction may be homologous with traits associated with radii and sticky spirals in aranoid orb webs. The numerous convergences between the webs and building behavior of young L. geometricus and the highly modified webs and building behavior of genera of the orb weaving families Theridiosomatidae (Wendilgarda) and Anapidae (Comaroma), which have independently replaced orbs with webs designed to capture prey on surfaces near the web, suggest a new hypothesis for how gumfoot theridiid webs may have evolved from orbs.